Determinación de la Concentración de Material Particulado Sedimentable generado en el Cantón Colta, Sector Majipamba - Puetate Alquinga, Luis David (2024)
This research objective is to determine the concentration of sedimentable particulate matter in the Majipamba community in the Colta canton, an area characterized by agriculture, forestry, fishing, and mining activities. In this research, 23 sampling points were established throughout the study area, distributed homogeneously to cover the points of most significant influence, locating the greatest number of sampling stations according to wind direction. The passive method was used to determine the amount of sedimentable particulate matter, which consists of placing Petri boxes with filter paper previously dried, weighed, and its area defined in each monitoring station in a period of 30 days (January - February 2023); to later perform the morphological and molecular analysis; in addition, the Geographic Information System (GIS) software was used to create the dispersion map of sedimentable particulate matter through the KRIGING interpolation tool, using the data of the concentrations of PMS, wind speed and wind direction. The results obtained show that the concentrations of monitoring stations 1 (0,51 mg/cm2 /month) and 19 (0,56 mg/cm2 /month) present values that exceed the maximum permissible limits established by the WHO (0,5 mg/cm2 /month). In contrast, the minimum concentration recorded was 0,10 mg/cm2 /month. The morphological and molecular analysis of two samples indicates that the observed particles present irregular, rounded, flat, and porous shapes, with sizes ranging between 16,15 and 91,70 microns; the chemical composition shows the presence of several elements such as O, Si, Al, Ca, N, Na, Fe, K, Mg and Ti of anthropogenic and natural origin, where the primary emission sources are vehicular traffic, construction works, and agricultural activities. Finally, the geostatistical analysis shows the behavior of the PMS with a northward dispersion.